Physical Activity Levels of a Multi-Ethnic Population of Young Men Living in Saudi Arabia and Factors Associated With Physical Inactivity - Jozaa Z. AlTamimi; Reham I. Alagal; Nora M. AlKehayez; Naseem M. Alshwaiyat; Hamid A. Al-Jamal; Nora A. AlFaris (Frontiers Media S.A., 2022)
ObjectiveRegular physical activity is essential for lifelong optimal health. Contrarily, physical inactivity is linked with risk for many chronic diseases. This study was conducted to evaluate the physical activity levels and factors associated with physical inactivity among a multi-ethnic population of young men living in Saudi Arabia.MethodsThis is a cross-sectional study involving 3,600 young men (20-35 years) living in Riyadh, Saudi Arabia. Sociodemographic and physical activity data were collected from subjects by face-to-face interviews. Physical activity characteristics were evaluated by using the Global Physical Activity Questionnaire. Weight and height were measured following standardized methods, then body mass index was calculated.ResultsPhysical inactivity was reported among 24.9% of study subjects. The lowest and highest rates of physical inactivity were reported among subjects from the Philippines (14.0%) and Saudi Arabia (41.5%), respectively. There is a high variation in daily minutes spent on physical activities related to work, transport, recreation, vigorous and moderate-intensity physical activities and sedentary behaviors among study participants based on their nationalities. Nationality, increasing age, longer residency period in Saudi Arabia, living within a family household, having a high education level, earning a high monthly income, and increasing body mass index were significantly associated with a higher risk of physical inactivity among the study participants.ConclusionPhysical inactivity prevalence is relatively high among a multi-ethnic population of young men living in Saudi Arabia. The findings confirmed notable disparities in the physical activity characteristics among participants from different countries living in Saudi Arabia.